Hipotermia terapéutica post-reanimación cardiopulmonar prolongada en paro cardiaco debido a tromboembolismo pulmonar. Reporte de caso (2014)
ABSTRACT: This is a report of a 41-year-old patient undergoing femur osteosynthesis (OS) who develops intraoperative cardiac arrest (CA) with pulseless electrical activity (PEA). Massive pulmonary thromboembolism (PTE) was diagnosed as the cause for the CA and a thrombolysis performed 30 min later reestablished spontaneous circulation with no new CA events. Therapeutic hypothermia (TH) was then established with local measures for 18 h for brain protection. The patient was extubated 24 h later with no neurological deficit. There is an increasing evidence of TH and its protective mechanisms in patients with non-shockable arrest rhythms leading to a widespread use of the technique in various institutions around the world, with particular emphasis on neurological outcomes. This article discusses a review of the current literature on TH, in addition to describing each of the stages in TH and how to approach these stages.